Morphometry of Mango Varieties and Sociodemographic Factors Influencing Mango Production in Uganda - Nakisozi, Henriettah; Ogwok, Patrick; Mugampoza, Diriisa (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Mangoes are Uganda’s most extensively distributed fruit crop. This study documented the morphological characteristics of mango fruit varieties and farming practices aimed at developing value-added food products. A total of 390 mango growers participated in the survey. A digital weighing scale and Vernier caliper were used to measure the morphological characteristics of mango fruits at physiological maturity. Twenty-two mango varieties were identified. Kagoogwa, Apple mango, and Doodo were the common varieties grown by over 30% of the growers. Kent, Tommy Atkins, and Bire were also widely grown, as reported by over 20% of growers. Of the six commonly grown varieties, four were indigenous, namely, Kagoogwa, Apple mango, Doodo, and Bire. Kent recorded the highest fruit weight (830.00 g) and Koona had the lowest (107.50 g). Principal component (PC) analysis showed that PC1 and PC2 explained 85.93% of the overall variation in data. PC1 explained 76.06% of the variation and PC2 accounted for 9.87%. Both PC1 and PC2 were positively linked to fruit and pulp weights. However, PC1 had a substantial influence with an eigenvalue of 5.32 while PC2 had an eigenvalue of 1.69. Non-indigenous varieties were larger (p<0.05) and had more pulp than indigenous varieties. The study provides insights into mango diversity in Uganda and highlights the potential for commercial exploitation of these fruits in the development of nutrient-rich food products.